Prognosis of Sentinel Node Staged Patients with Primary Cutaneous Melanoma - Elsaeßer, Otmar; Leiter, Ulrike; Buettner, Petra G.; Eigentler, Thomas K.; Meier, Friedegund; Weide, Benjamin; Metzler, Gisela; Breuninger, Helmut; Garbe, Claus (PLOS ONE, 2012)
Background This study investigated survival probabilities and prognostic factors in sentinel lymph node biopsy (SLNB) staged patients with cutaneous melanoma (CM) with the aim of defining subgroups of patients who are at higher risk for recurrences and who should be considered for adjuvant clinical trials. Methods Patients with primary CM who underwent SLNB in the Department of Dermatology, University of Tuebingen, Germany, between 1996 and 2009 were included into this study. Survival probabilities and prognostic factors were evaluated by Kaplan-Meier and multivariate Cox proportional hazard models. Results 1909 SLNB staged patients were evaluated. Median follow-up time was 44 months. Median tumor thickness was 1.8 mm, ulceration was present in 31.8% of cases. The 5-year Overall Survival (OS) was 90.3% in SLNB negative patients (IB 96.2%, IIA 87.0%, IIB 78.1%, IIC 72.6%). Patients with micrometastases (stage IIIA/B) had a 5-year OS rate of 70.9% which was clearly less favorable than for stages I–II. Multivariate analysis revealed tumor thickness, ulceration, body site, histopathologic subtype and SLNB status as independent significant prognostic factors. Conclusion Survival rates of patients with primary CM in stages I–II were shown to be much more favorable than previously reported from non sentinel node staged collectives. For future clinical trials, sample size calculations should be adapted using survival probabilities based on sentinel node staging.